Research on Heat Pipe Radiator of CRH2 EMUs CI - LI Chun-yang; XIAO Ning; YANG Hong-sheng (机车电传动)
Development process, product performance, features and application prospects of the heat pipe radiator for CRH2 EMUs’ CI were describled. With comparison to H1X3206, domestic heat pipe radiator DG7027 has achieved and exceeded the requirement value of parts imported from Japan. After completion of type test for each item, it can realize batch production.